The End Of The Kokand Khanate By The Russian Empire And The Formation Of The Ferghana Region As Represented In Sources - Khilolakhon Parvozbek kizi Khakimjonova (Zien Journals, 2025)
This article reflects the work done by the Russian Empire to conquer the Kokand Khanate, the organization of the Ferghana region, and the policy pursued by the ruling Kokand Khan Khudoyar Khan during the period of the threat posed by the Russian Empire
Keywords: Russian Empire; Kokand Khanate; Khudoyar Khan